Inherent Relationship Between Transport Costing and Organizational Competitiveness: A Case of the Road Freight Sector in Zimbabwe - Tapiwa Christopher Mujakachi; Marian Tukuta; Maria Tsvere (ExcelingTech, 2023)
The main aim of road freight transport is transporting of goods by road. It is the most developed area of transport. The advantage of road transport is the direct transport from the sender to the recipient, faster, easier transportation resulting from technology, availability and operability. The disadvantages of this type of transport are traffic intensity dependence on the state network of road infrastructure and negative impact on the environment. The significance of calculation in transport is so important. It helps carriers to inform on the efficiency and profitability of the services provided, also in allocation of pricing services for budgetary purposes, but also for reducing of cost. This study interrogated the inherent relationship between transport costing and organizational competitiveness in the Zimbabwe Road Freight Sector. The study was prompted by an observation that most road freight companies collapsed before even they reach the five-year mark of trading. Literature is awash with transport costing models and there seemed to be a disparity in the conceptualization and application of these to real business scenarios. That led to the use of somewhat firefighting costing strategies with no meaning results. This was a quantitative study of road freight transport sector across Zimbabwe with a population of 1256 registered companies and a randomly picked sample size of 384. A total of 384 questionnaires were distributed and 291 were retrieved giving a response rate of 75.6%. study found out that the idea of transport costing was alien in the minds of many operators and managers as they used borrowed rates from competitors to price their own services without looking at the cost build up to the rate. This led to unprofitable operations. The study findings established that transport costing has a positive effect on organizational competitiveness. The study recommends training and development into transport costing and inclusion of this concept as a stand-alone module in Zimbabwean Education curriculum.